Ecological Analysis of Stroke in Indonesia in 2018 - Izza Dinalhaque Pranatasari; Agung Dwi Laksono (Institute of Medico-legal Publications Pvt Ltd, 2021)
Stroke is one of the significant causes of disability and death worldwide and is classified as a catastrophic disease in Indonesia. The study aims to analyze ecologically the factors related to theprevalence of stroke in Indonesia. The authors conduct a research using secondary data from the 2018 Indonesia Basic Health Survey that used all the provinces as samples. Apart from theprevalence of stroke, four other variables analyzed as independent variables were diabetes mellitus, theprevalence of hypertension, theprevalence of obesity, and the percentage of the population with alcohol consumptionin the past month. Data were analyzed using a scatter plot.The study results found thatthe higher the prevalence of diabetes mellitus, hypertension, and obesity in a province, the higher the prevalence of stroke. However, the higher the population percentage with alcohol consumption, the lower the prevalence of stroke in that province. The three variables, which are the prevalence of diabetes mellitus, hypertension, and obesity, were positively related to the prevalence of stroke in Indonesia. The population percentage with alcohol consumption was negatively associated with the majorityof stroke in Indonesia.